2017
DOI: 10.1051/metal/2017048
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on cold work of AISI D2 tool steel

Abstract: As a common material in mould and die application, AISI D2 cold work tool steel has proven to be a promising chosen material in the industries. However, challenges remain in using AISI D2 through a modified version with a considerable progress having been made in recent years. This paper provides a critical review of the original as-cast AISI D2 cold work tool steel up to the modified version. The main purpose is to develop an understanding of current modified tool steel trend; the machinability of AISI D2 (dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The second group of steels investigated in this study comprises classes that, in addition to martensite and retained austenite in the quenched state, also contain undissolved carbides (eutectic; secondary) (Figure 2b, [98]). Ball bearing steels, ledeburitic cold work tool steels [99][100][101][102][103][104][105][106][107][108][109][110], or high-speed steels [111][112][113] are typical examples.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…The second group of steels investigated in this study comprises classes that, in addition to martensite and retained austenite in the quenched state, also contain undissolved carbides (eutectic; secondary) (Figure 2b, [98]). Ball bearing steels, ledeburitic cold work tool steels [99][100][101][102][103][104][105][106][107][108][109][110], or high-speed steels [111][112][113] are typical examples.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…This alloy's special qualities have made it valuable across various sectors. Die, trimming, coining, punching, shear blades, fuller, Phillips head forming dies, thermosetting resin forming dies, cold forming dies, fine blanking, stripper plates, brick molds, chisels, pneumatic tools, deep drawing and forming dies, cold drawing punches, hobbing, blanking, lamination and stamping dies, shear blades, burnishing rolls, master tools and gauges, slitting cutters, thread rolling & wire is just a few of the many uses for AISI D2 2 4 . It was observed that the dielectric oil waste generated at the end of the EDM operation was very toxic and could not be reused, making the EDM process unsustainable.…”
Section: Introductionmentioning
confidence: 99%
“…M2 is a specific grade of HSS, prized for its exceptional wear resistance and high hardness retention at elevated temperatures. It is extensively utilized in cutting tools, drills, taps, and various high-speed machining applications [42][43][44][45][46][47]. Quantifying carbides in M2 tool steel processed via BJ is paramount, given its profound implications for material performance, quality assurance, and process optimization within the AM realm.…”
Section: Introductionmentioning
confidence: 99%